Intelligent document capture with Ephesoft : automate the processing of scanned and digital documents by improving accuracy using web-based open and modern intelligent document capture software /: automate the processing of scanned and digital documents by improving accuracy using web-based open and modern intelligent document capture software. (2015) - Myers, Pat
No abstract available